Combined experimental and quantum computational studies on 5-Fluorouracil salicylic acid cocrystal: Assessment on anti-breast cancer potential through docking simulation - Karuppasamy, Jayapriyanga; Zochedh, Azar; Al-Asbahi, Bandar Ali; Kumar, Yedluri Anil; Shunmuganarayanan, Athimoolam; Sultan, Asath Bahadur (Journal of molecular structure, 2024)
•5FUSA was synthesized and characterized thru XRD, FTIR and UV spectroscopy.•FMO, MEP, Mulliken, Fukui, Thermodynamics and NBO were analysed via DFT.•Topological properties were studied based on ELF, LOL and RDG analysis.•Intermolecular interactions were studied through Hirshfeld surface analysis.•Anticancer potential of 5FUSA was investigated through molecular docking. 5-fluorouracil salicylic acid (5FUSA) cocrystal was synthesised via mechanochemical and solution evaporation technique and spectroscopic experiments and theoretical research were conducted. Methods for the experiments included XRD, FTIR, and UV spectroscopy. Following that, 5FUSA was the subject of quantum chemistry investigations employing the DFT/B3LYP/6–311++G (d, p) basis level. First, the resultant simulated XRD pattern was compared to the relevant experimental pattern. The estimated FT-IR frequencies were gathered from the same level of theory and compared to the experimental data. To learn more about the reactive properties of the 5FUSA, the molecular electrostatic potential plot was generated, and Fukui function calculations were also performed. In order to examine intramolecular interactions and verify the bioactivity of the 5FUSA molecule, the natural bond orbital study was also carried out. We examined the UV–Vis absorption wavelengths (λ) via theoretical (TD-DFT) and experimental methods. The non-linear optical properties were identified, and it was discovered that it had three times the NLO activity of urea. The inter- and intramolecular interactions of the 5FUSA were explored using the Hirshfeld surface and finger print approaches. At various temperatures thermodynamic parameters were calculated and topological analyses were conducted using the (ELF, LOL, and RDG). The anticancer activity of 5FUSA cocrystal was studied using molecular docking and the docking scores ranges between -8.1 to -9.0 Kcal/mol against breast tumor proteins. [Display omitted]